STRATEGI BLUE OCEAN DALAM PENERAPAN EKONOMI KREATIF - Hendarsih, Ida (www.bsi.ac.id, 2016)
Intense market competition requires businesses to be creative and innovative in developing production and marketing strategy. One idea management activities the company's strategy is to apply a blue ocean strategy in a creative and innovative efforts to develop the productivity of services and goods. Viewing conditions were increasingly crowded market by producing the same type of production, the business competition is getting tougher. At present this is not just a marketing strategy standards are needed businesses to win the market competition, but businesses are required to be more creative in producing and venture out of the comfort zone to create a new breakthrough product models that have never been thought of before by competitors . Implementation improve the creative economy needed a grand design of products for the development of creative industries in all fields. Creative economy that include the creative industries, in many countries today is believed to contribute significantly to the economy of the nation. Businesspersons are encouraged to look into an arena of new creative products, new markets that are potentially far ignored by competitors. Creative economy which focuses on the creation of goods and services by relying on the expertise, talent, and creativity as intellectual property, is the hope for the Indonesian economy to rise, compete and achieve excellence in the global economyKeywords: Blue Ocean, creative economy